Digital Communications 2 - Assad, Safwan; Barba, Dominique (Wiley-ISTE, 2020)
It is a complete training in digital communications in the same book with all the aspects involved in such training: courses, tutorials with many typical problems targeted with detailed solutions, practical work concretely illustrating various aspects of technical implementation implemented. It breaks down into three parts. The Theory of information itself, which concerns both the sources of information and the channels of its transmission, taking into account the errors they introduce in the transmission of information and the means of protect by the use of appropriate coding methods. Then for the technical aspects of transmission, first the baseband transmission is presented with the important concept and fundamental technique of equalization. The performance evaluation in terms of probability of errors is systematically developed and detailed as well as the online codes used. Finally, the third part presents the Transmissions with digital modulation of carriers used in radio transmissions but also on electric cables. A second important aspect in learning a learner's knowledge and skills is this book. It concerns the "Directed Work" aspect of a training. This is an ordered set of 33 typical problems with detailed solutions covering the different parts of the course with practical work. Finally, the last aspect concerns the practical aspects in the proper sense of the term, an essential complement to training going as far as know-how. We propose here a set of 5 practical works.